Subcorneal Pustular Dermatosis with Temporary Autoimmune Features during COVID-19 Pandemic - Wollina, Uwe; Koch, André; Hansel, Gesina; Fürll, Caroline; Schönlebe, Jacqueline (Open Access Macedonian Journal of Medical Sciences, 2020)
Subcorneal pustular dermatosis, Sneddon-Wilkinson, is an uncommon neutrophilic dermatosis of unknown etiology. We report on a 51-year-old woman who presented with multiple superficial erythematous erosions surrounded by annular arranged sterile pustules concentrated on the trunk, the neck, and the proximal extremities during the coronavirus disease-19 pandemic. Larges pustules and flaccid bullae showed a hypopyon. There were no fever and no pruritus, general health was unaffected. Laboratory investigations revealed leukocytosis, neutrophilia, lymphopenia, and increased C-reactive protein. Initially, antinuclear antibodies, pemphigoid antibodies, and antibodies to BP 230 were positive, but negative 5 days later. Nasopharyngeal swabs were negative for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA tested by real-time reverse-transcriptase-polymerase chain reaction. A diagnostic skin biopsy showed epidermal spongiotic vesiculation and subcorneal pustulation with acantholysis and an inflammatory infiltrate composed of neutrophils and lymphocytes. The confirmed diagnosis was subcorneal pustular dermatosis Sneddon-Wilkinson. She was treated by dapsone and corticosteroids with the latter tempered down. Clinical response was rapid. We suggest that the autoimmune features seen on admission may be due to an undefined viral infection, but not SARS-CoV-2.